Quantitative Approaches in Business Studies - Clare Morris (England Pearson, 2012)
Quantitative Approaches in Business Studies provides a clear and accessible introduction to quantitative methods, ideal for students of business and management on undergraduate, Masters and professional courses. With a uniquely user-friendly style, Clare Morris' popular treatment of this challenging subject is carefully designed to build students' confidence in the use and interpretation of quantitative methods. Encouraging conceptual understanding as well as practical aptitude, the text leads the reader from an initial chapter revising basic mathematics through to a concluding chapter discussing statistical research methods for student projects. Practical guidance on the use of Excel for quantitative analysis runs throughout the text, integrated with an online Excel workbook. New for this edition Access to MyMathLab Global, an unrivalled online tutorial and assessment system. Many new 'Quantitative Methods in Practice' examples, drawn from recent and topical articles in the press and beyond. Substantial case-studies at the end of each chapter, integrating the material of the chapter. Revised and updated throughout. MyMathLab Global will generate a personalised study plan for you and provide extensive practice questions exactly where you need them. Interactive questions with randomised values allow you to practise the same concept as many times as you need until you master it. Guided solutions break down the question for you step-by-step.
Keywords: Business; (UGB-108) Quantitative Methods for Business